1p/19q testing has no significance in the workup of glioblastomas - Clark, K. H. (2013)
AIMS: To determine whether testing for isolated 1p or 19q losses, or as a codeletion, has any significance in the workup of glioblastomas (GBMs). METHODS: Upfront 1p/19q testing by fluorescence in situ hybridization (FISH) and/or polymerase chain reaction (PCR)-based loss of heterozygosity (LOH) was done in 491 gliomas that were histologically diagnosed as GBMs. Outcomes were determined and measured against 1p/19q results. RESULTS: Twenty-eight showed apparent 1p/19q codeletion by either FISH and/or PCR-based LOH, but only 1/26 showed codeletion by both tests. Over 90% of tumours with apparent codeletion by either FISH or LOH also had 10q LOH and/or EGFR amplification, features inversely related to true whole-arm 1p/19q codeletion. Furthermore, only 1/28 tumours demonstrated an R132H IDH1 mutation. Neither 1p/19q codeletion by FISH nor LOH had an impact on GBM survival. Isolated losses of 1p or 19q also had no impact on survival. CONCLUSIONS: These data suggest that (i) 1p/19q testing is not useful on gliomas that are histologically GBMs; (ii) codeletion testing should be reserved only for cases with compatible morphology; and (iii) EGFR, 10q, and IDH1 testing can help act as safeguards against a false-positive 1p/19q result.